2012
DOI: 10.1038/bcj.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors influencing clinical outcome of allogeneic hematopoietic stem cell transplantation following imatinib-based therapy in BCR–ABL-positive ALL

Abstract: We investigated prognostic factors for the clinical outcome of allogeneic hematopoietic stem cell transplantation (allo-HSCT) in patients with Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ALL) following imatinib-based therapy. Among 100 adult patients who were prospectively enrolled in the JALSG Ph+ALL202 study, 97 patients obtained complete remission (CR) by imatinib-combined chemotherapy, among whom 60 underwent allo-HSCT in their first CR. The probabilities of overall survival (OS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
5
20
1
2
Order By: Relevance
“…These results confirm the observations made in our previous study based on the use of dasatinib in induction, 16 and are in line with the current general knowledge on the prognostic impact of MRD. 12,19,[37][38][39][40][41][42][43] Furthermore, they strengthen the notion that MRD negativity should be regarded as a major goal in Ph + ALL treatment. Indeed, with few exceptions, 20,38 it is now well established that BCR-ABL1 transcript levels correlate with response.…”
supporting
confidence: 60%
“…These results confirm the observations made in our previous study based on the use of dasatinib in induction, 16 and are in line with the current general knowledge on the prognostic impact of MRD. 12,19,[37][38][39][40][41][42][43] Furthermore, they strengthen the notion that MRD negativity should be regarded as a major goal in Ph + ALL treatment. Indeed, with few exceptions, 20,38 it is now well established that BCR-ABL1 transcript levels correlate with response.…”
supporting
confidence: 60%
“…In this largest sample study, we extended the established MRD experience in the MDST, MUDT, and CBT settings and showed that, in unmanipulated haplo‐SCT modality, ( a ) pre‐MRD status was associated with a higher incidence of relapse as well as lower LFS and OS; ( b ) the levels of pre‐MRD were also correlated with CIR, LFS, and OS; and ( c ) a scoring system that could be used in predicting transplant outcomes, including relapse, LFS, and OS, was effectively established based on pre‐MRD. Our study adds novel evidence, suggesting that the incorporation of MRD platforms into the monitoring of patients with ALL pretransplantation is a transformative approach in the risk stratification of cases with this clinically challenging disease.…”
Section: Discussionmentioning
confidence: 96%
“…In allo‐SCT settings, the importance of pretransplantation MRD (pre‐MRD) status is gaining appreciation based on several publications showing significantly inferior outcomes for ALL patients with positive pre‐MRD, and possibly, the clinical benefit accrued by an allo‐SCT in ALL patients with a suboptimal MRD response to initial induction chemotherapy . However, these studies, with heterogeneous conditioning regimen, stem cell source, and graft‐vs‐host disease (GVHD) prophylaxis, mainly focused on human leukocyte antigen (HLA)‐matched related (MSDT) and unrelated donor transplantation (MUDT) as well as cord blood transplantation (CBT) . With the increased use of haploidentical SCT (haplo‐SCT) in ALL patients, it is becoming increasingly imperative to determine the role of pre‐MRD studies may assume in prognostication of patients with ALL who underwent haplo‐SCT.…”
Section: Introductionmentioning
confidence: 99%
“…As clinical trial in Japan, 60 patients received allo-HCT in CR1 in the JALSG Ph+ALL202 study (registered between September 2002 and May 2005) 20 and 43 patients received allo-HCT in CR in the Japan Adult Leukemia Study Group (JALSG) Ph+ALL208IMA study (registered between October 2008 and December 2010). 21 Additional data for the use of pre-and post-transplant TKI administration and MRD at and after allo-HCT were collected for this study.…”
Section: Patientsmentioning
confidence: 99%